# mathematics: algebra;equations

posted by .

-12 + 5u= -48

• mathematics: algebra;equations -

-12 + 5u= -48
5u = -48+12
5u = -36
divide both sides by 5
u = -36/5

• mathematics: algebra;equations -

-12 + 5u= -48

-12 + 12 + 5u = -48 + 12
5u = -36
u = -7.2

Check it out:

-12 + (-36) = -48
-48 = -48

## Similar Questions

1. ### algebra

Solve the given equations: 1. |2x-5|= 29 Answer: x=17 or is it........ x=-12 2. 5(x+3)-2x = -21 Answer: x=-12 3. 3x+3(1-x)= x-17 Answer: x=20 4. 2[1-3(x+2)] = -x Answer: x= -2 Factor Completely: 1. x^2-12x+20 Answer: (x-2)(x-10) 2. …
2. ### math

wuts 2.5 times 70? put 2.5*70 into Google and see what you get think of it like this: 70 x 2.5 ______
3. ### algebra

1)What is the 4x^2=y^2+8y+32 answer= either hyperbola or parabola 2)The graph of which equation is a circle?
4. ### Algebra

I am solving sytems of equations algrbraically. I have tried several times and I am not comming up with he answers for the following three equations that the book gives. 1) 4x-2y=-5 -x+2y=2 Answer in book: -1,1/2 2) -5x+2y=10 5x-3y=-10 …
5. ### Algebra 2

Can someone check my answers. Write the following equations in standard form. 1) x^2 - 2x + y^2 + 4y = 11 answer: (x-1)^2 + (y+2)^2 = 16 2) 4x^2 + 24x - y + 34 = 0 answer: y = 4(x-3)^2 + 2 3) The graph of which equation is a circle?
6. ### algerbra!

23+3J=35 wuts j
7. ### Math

wuts the simple form the expression 8x-2+5-5x-2+3?
8. ### math

1. Select any two integers between -12 and +12 which will become solutions to a system of two equations. 2. Write two equations that have your two integers as solutions. Show how you built the equations using your integers. Your solution …
9. ### Mathematics

Q 1 . Change the following polar equations into Cartesian equations: (a) r = a sin 2 A (b) A=π/4
10. ### Applied Mathematics and Computation

I have these equations, Equation 1: F(x^k)/F'(x^k) = e^k - ((1/(2!))(F''(x^k))((e^k)^2))/(F'(x^k)) + ((1/(3!))(F'''(x^k))((e^k)^3))/(F'(x^k)) - ((1/(4!))(F''''(x^k))((e^k)^4))/(F'(x^k)) + O(||e^k||^5) Equation 2: (y^k) - (x^k) = -[e^k …

More Similar Questions